Shelf and deep-water benthic macrofauna assemblages from the western Gulf of Mexico: Temporal dynamics and environmental drivers. (March 2021) - Hernández-Ávila, Iván; Pech, Daniel; Ocaña, Frank A.; Árcega-Cabrera, Flor; Enriquez, Cecilia
Abstract: Shelf and deep-water soft-bottom macrofauna were explored in the western Gulf of Mexico in terms of species and functional trait assemblages. Their variation was analysed as functions of depth and time, and the relationship with sea-bottom environmental conditions was examined to disentangle their association with potential environmental drivers. Four consecutive cruises (two per year, at the end of the dry and rainy seasons) were performed during 2016–2017 at 27 fixed stations distributed from 42 to 3565 m depth. Changes in macrofauna composition were tested considering species and functional trait assemblages. Environmental variables associated with sediment features (i.e., grain structure, organic matter, pH, redox), oceanographic conditions (i.e., temperature, dissolved oxygen, particulate organic carbon flux) and potential contaminants (i.e., hydrocarbons and metals) were analysed to identify potential drivers that would shape the structure of macrofauna assemblages. The results suggest that the structures of both species and functional trait assemblages change according to depth and show temporal variation in composition at seasonal and interannual scales. The effect of temporal variation represented about 12% of total variation in the assemblages (11.4 for species and 12.5% for functional-traits). Different patterns of spatial and temporal variation between shelf and deep benthic communities were observed. Variation in species assemblages on the shelf were related to the variation in lead, polycyclic aromatic hydrocarbons and the fine sand ratio. In the deep benthos, particulate carbon flux showed high correlation with the spatial and temporal variation in species assemblage. In the deep benthos the changes in the species assemblage between the dry and the rainy seasons and the interannual variation were highly correlated with particulate organic carbon input in the area. Highlights: Shelf and deep-water macrofauna show seasonal and interannual variation in both species and functional trait assemblages. Changes in assemblage composition were correlated with environmental conditions, according to depth range. Variation on the shelf benthic macrofauna was associated with bottom oxygen, POC flux, PAHs and lead concentration. Changes on deep-water assemblage composition were highly correlated with POC flux.